2015
DOI: 10.4212/cjhp.v68i3.1458
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus Oral Acetaminophen for Pain: Systematic Review of Current Evidence to Support Clinical Decision-Making

Abstract: Background: Intravenous (IV) acetaminophen is increasingly used around the world for pain control for a variety of indications. However, it is unclear whether IV administration offers advantages over oral administration. Objective: To identify, summarize, and critically evaluate the literature comparing analgesic efficacy, safety, and pharmacokinetics for IV and oral dosage forms of acetaminophen. Data Sources: A literature search of the PubMed, Embase, and International Pharmaceutical Abstracts databases was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 25 publications
3
75
0
1
Order By: Relevance
“…Although the intravenous preparation is often anecdotally regarded as superior, our results demonstrating no difference are congruent with a recent systematic review comparing oral and intravenous paracetamol in a variety of settings 9. These authors included six randomised trials in the review, only three of which assessed efficacy outcomes and all were in the postoperative setting.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the intravenous preparation is often anecdotally regarded as superior, our results demonstrating no difference are congruent with a recent systematic review comparing oral and intravenous paracetamol in a variety of settings 9. These authors included six randomised trials in the review, only three of which assessed efficacy outcomes and all were in the postoperative setting.…”
Section: Discussionsupporting
confidence: 86%
“…Analgesics such as oral paracetamol, oxycodone and non-steroidal anti-inflammatory drugs are used as adjuncts or for less severe pain presentations. An intravenous preparation of paracetamol has been available for 10–15 years, although availability in EDs is often restricted 9. In the ED setting, intravenous paracetamol has been compared with intravenous morphine and other active comparators, with conflicting results 10–13.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even though intravenous paracetamol seems better in terms of pharmacokinetics profile studies have shown that differences in plasma exposure between routes of administration may not necessarily result in differences in clinical outcomes. 16 Limitation in our study was plasma levels of the drug were not measured at corresponding pain score level. We used only single dose of rectal paracetamol for post-operative pain, as tonsillectomy results only in mild-to-moderate pain relief and is unnecessary leading to physical discomfort.…”
Section: Discussionmentioning
confidence: 84%
“…The addition of acetaminophen to opioid-based postoperative pain management results in a reduction in opioid consumption of 20–40% over the first 24 hours after various major and minor surgical procedures (20)(21,22) (12,23). Whether efficacy of acetaminophen differs by route of administration is controversial; although some studies suggest benefit to IV acetaminophen (24), the majority of studies have not shown any significant benefit to the administration of IV over oral acetaminophen in decreasing opioid use (2527). There are also currently no high quality data specifically demonstrating the impact of postoperative acetaminophen on opioid consumption after reproductive/gynecologic surgery, but it is likely that the benefits observed for other surgeries will translate.…”
Section: Non-opioid Analgesicsmentioning
confidence: 99%